Toward spatial glycomics and glycoproteomics: Innovations and applications - Patcharaporn Boottanun; Sayaka Fuseya; Atsushi Kuno (BBA Advances)
In this mini review, we provide an overview of the challenging field of spatial glycomics/glycoproteomics. Owing to their complexity, sophisticated analytical methods and innovative technologies are needed to advance this field. An agile development approach enables unraveling aberrant glycosylations, glycobiomarkers, and glycotargets for spatial imaging, diagnosis, and therapeutic purposes. We discuss glycopathology and tissue glycomic profiling using highly sensitive lectin-based analyses and introduce deep visual proteomics for glycomic/glycoproteomic sample preparation. Additionally, we highlight the importance of leveraging laser microdissection and artificial intelligence-driven visual software for cell-type assignment and automation techniques, which are crucial for advancing glycomics/glycoproteomics.